Protein kinase Cθ is required for cardiomyocyte survival and cardiac remodeling - Paoletti, R; Maffei, A; Madaro, L; Notte, A; Stanganello, E; Cifelli, G; Carullo, P; Molinaro, M; Lembo, G; Bouché, M (Cell death & disease, 2010)
Protein kinase Cs (PKCs) constitute a family of serine/threonine kinases, which has distinguished and specific roles in regulating cardiac responses, including those associated with heart failure. We found that the PKC θ isoform is expressed at considerable levels in the cardiac muscle in mouse, and that it is rapidly activated after pressure overload. To investigate the role of PKC θ in cardiac remodeling, we used PKC θ −/− mice. In vivo analyses of PKC θ −/− hearts showed that the lack of PKC θ expression leads to left ventricular dilation and reduced function. Histological analyses showed a reduction in the number of cardiomyocytes, combined with hypertrophy of the remaining cardiomyocytes, cardiac fibrosis, myofibroblast hyper-proliferation and matrix deposition. We also observed p38 and JunK activation, known to promote cell death in response to stress, combined with upregulation of the fetal pattern of gene expression, considered to be a feature of the hemodynamically or metabolically stressed heart. In keeping with these observations, cultured PKC θ −/− cardiomyocytes were less viable than wild-type cardiomyocytes, and, unlike wild-type cardiomyocytes, underwent programmed cell death upon stimulation with α 1-adrenergic agonists and hypoxia. Taken together, these results show that PKC θ maintains the correct structure and function of the heart by preventing cardiomyocyte cell death in response to work demand and to neuro-hormonal signals, to which heart cells are continuously exposed.